Simulação de um extrator industrial de óleo de soja - Polon, Paulo Eduardo (1997)
Industrially the soybean oil is produced by solvent extraction. Although the process is well known it needs to design and optimization of new plants. In this work it is analyzed the strategy of simulation for this process in the continuos countercurrent extractor, using hexane as solvent. The mathematical model used was presented by Spaninks and Bruin (1979), based in the analogy between crossflow and the fixed bed process column. The Differential Partial Equations (DPE) that describe the mass transfer in the fixed bed was used to represent the extraction in each step of equipment. To solve the DPE the finite method was used. The results obtained allow a good perception of the oil concentration variation in both solid and liquid phase, and it was compared with an industrial extractor. It was availed to the effect of changes in some process variables.